2009
DOI: 10.1007/s15010-008-8046-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Linezolid vs Vancomycin in Suspected Methicillin-Resistant Staphylococcus aureus Nosocomial Pneumonia in Germany

Abstract: The model estimated a higher clinical cure (+8.7%) and survival (+13.2%) for linezolid compared with vancomycin at an incremental cost of 420 per treatment episode. The cost-benefit profile suggests that linezolid could be considered a cost-effective alternative to vancomycin in the treatment of patients with NP caused by suspected MRSA in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Since linezolid has a similar MIC to vancomycin for resistant bacteria (approximately 0.25-0.5 ug/ml [9,32]) it is likely that these release profiles will provide above MIC levels of linezolid at treatment sites. Since linezolid is almost four times as expensive as vancomycin [11] and the sustained release of large amounts of the drug is particularly important to prevent the development of resistance, these data support the inclusion of excipients like salt in linezolid-loaded cement.…”
Section: Resultsmentioning
confidence: 78%
“…Since linezolid has a similar MIC to vancomycin for resistant bacteria (approximately 0.25-0.5 ug/ml [9,32]) it is likely that these release profiles will provide above MIC levels of linezolid at treatment sites. Since linezolid is almost four times as expensive as vancomycin [11] and the sustained release of large amounts of the drug is particularly important to prevent the development of resistance, these data support the inclusion of excipients like salt in linezolid-loaded cement.…”
Section: Resultsmentioning
confidence: 78%
“…35 Multiple studies have investigated the costeffectiveness of linezolid for MRSA pneumonia, [36][37][38][39] using pooled data from Rubinstein et al 22 and Wunderink et al 23 These studies conclude that, despite linezolid costs approximately 10 times that the Panton-Valentine Leukocidin (PVL) toxin associated with necrotizing pneumonias, 32,33 is the mechanism of putative superiority for linezolid. Importantly, the studies included in our meta-analysis focused on nosocomial MRSA pathogens, which are less likely to produce the PVL toxin, as compared with emerging community-acquired MRSA.…”
Section: Resultsmentioning
confidence: 99%
“…Previous economic studies have demonstrated that linezolid is more cost-effective than vancomycin for NP patients [33][34][35][36]; the clinical data used in those studies were from Rubinstein et al [24] and Wunderink et al [26]. However, Walkey et al [14] questioned the use of pooled data.…”
Section: Discussionmentioning
confidence: 99%